(untitled) (Scientific journal of the Fergana State University, 2024)
In this state, the development of a new Uzbekistan is the only true way to improve the quality of education, introduce modern teaching methods at all levels of lifelong education systems, strengthen the material and technical base, and create new educational institutions. amenities and support for youth.